2012
DOI: 10.1111/j.1365-2702.2011.04063.x
|View full text |Cite
|
Sign up to set email alerts
|

Key components of a service model providing early childhood support for women attending opioid treatment clinics: an Australian state health service review

Abstract: Reduction of access difficulties to specialised early childhood support is of benefit to clients, community health services attempting to provide a service to this difficult to reach population and to drug and alcohol services seeking to provide a high level of holistic care for clients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…A constant and real fear of the removal of their children from their care exists, resulting in some of the participants restricting their access with health‐ and other community‐based services (Harvey et al . ). For many of the participating women, the language and comments used by health professionals and others exacerbated their feelings of guilt and fear.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A constant and real fear of the removal of their children from their care exists, resulting in some of the participants restricting their access with health‐ and other community‐based services (Harvey et al . ). For many of the participating women, the language and comments used by health professionals and others exacerbated their feelings of guilt and fear.…”
Section: Discussionmentioning
confidence: 97%
“…Yet mothers with a history of substance dependence and their families, in particular, can experience difficulties accessing these child and family health services because of a variety of complex and hidden barriers (Huxley & Foulger , Harvey et al . ), which may include the sense of being constantly under surveillance (Silva et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Identification of the facilitators and barriers to care between both sites highlighted the differences in pathways to care and may shed light on the possible reasoning behind the differing attendance rates. Typically this group is difficult to engage in post-natal care [7]. Nehra's study found that, in the general neonatal population, factors that significantly improved compliance included having patient contact after discharge, and also giving early intervention referral.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the role of the child and family health nurse in engaging this particular group has been well documented. CFHN staffs are in a unique position to be able to build trusting relationships, offer continuity of care and assist in accessing health care systems [7,24,25]. In relation to hospital visits, these were higher in Site A, where attendance at clinic was lower and communication between hospital and community services specific to this vulnerable group was less structured.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation